A Decade of Molecular Understanding of Withanolide Biosynthesis and In vitro Studies in Withania somnifera (L.) Dunal: Prospects and Perspectives for Pathway Engineering - Dhar, Niha; Razdan, Sumeer; Rana, Satiander; Bhat, Wajid W.; Vishwakarma, Ram; Lattoo, Surrinder K. (Frontiers in Plant Science, 2015)
Withania somnifera, a multipurpose medicinal plant is a rich reservoir of pharmaceutically active triterpenoids that are steroidal lactones known as withanolides. Though the plant has been well characterized in terms of phytochemical profiles as well as pharmaceutical activities, limited attempts have been made to decipher the biosynthetic route and identification of key regulatory genes involved in withanolide biosynthesis. This scenario limits biotechnological interventions for enhanced production of bioactive compounds. Nevertheless, recent emergent trends vis-à-vis, the exploration of genomic, transcriptomic, proteomic, metabolomic and in vitro studies have opened new vistas regarding pathway engineering of withanolide production. During recent years, various strategic pathway genes have been characterized with significant amount of regulatory studies which allude towards development of molecular circuitries for production of key intermediates or end products in heterologous hosts. Another pivotal aspect covering redirection of metabolic flux for channelizing the precursor pool towards enhanced withanolide production has also been attained by deciphering decisive branch point(s) as robust targets for pathway modulation. With these perspectives, the current review provides a detailed overview of various studies undertaken by the authors and collated literature related to molecular and in vitro approaches employed in W. Somnifera for understanding various molecular network interactions in entirety.